Fundamentals of eccentric work - Hoppeler, H. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Concentric work denotes a muscle activation that results in shortening of the muscle. Concentric muscle action thus imparts kinetic or potential energy to the body or an object that is moved. By contrast, eccentric muscle activation denotes muscle activation during muscle lengthening. Under these conditions, negative work is done and the body or object moved is decelerated or is assisted in losing potential energy. Alpine skiing is a sport for which controlled eccentric muscle activation is key to success. During a race, as much as possible of the potential energy of the racer and his equipment needs to be converted into kinetic energy without losing control. To understand the physiology of eccentric exercise is therefore fundamental. There are a number of key features that distinguish eccentric from concentric muscle actions. This review highlights the most relevant physiological characteristics of eccentric muscle actions.